Determination of Diffusion Kinetics of Ketamine in Brain Tissue: Implications for in vitro Mechanistic Studies of Drug Actions - Geiger, Zachary; VanVeller, Brett; Lopez, Zarin; Harrata, Abdel K.; Battani, Kathryn; Wegman-Points, Lauren; Yuan, Li-Lian (Frontiers in Neuroscience, 2021)
Ketamine has been in use for over 50 years as a general anesthetic, acting primarily through blockade of N-methyl-D-aspartate (NMDA) receptors in the brain. Recent studies have demonstrated that ketamine also acts as a potent and rapid-acting antidepressant when administered at sub-anesthetic doses. However, the precise mechanism behind this effect remains unclear. We examined the diffusion properties of ketamine in brain tissue to determine their effects in in vitro studies related to the antidepressant action of ketamine. Brain slices from adult mice were exposed to artificial cerebrospinal fluid (aCSF) containing ~17 µM ketamine HCl for varying amounts of time. The amount of ketamine within each slice was then measured by tandem high-performance liquid chromatography – mass spectrometry (HPLC-MS) to characterize the diffusion of ketamine into brain tissue over time. We successfully modeled the diffusion of ketamine into brain tissue using a mono-exponential function with a time constant of τ=6.59 minutes. This curve was then compared to a one-dimensional model of diffusion yielding a diffusion coefficient of approximately 0.12cm2∙s-1 for ketamine diffusing into brain tissue. The brain:aCSF partition coefficient for ketamine was determined to be approximately 2.76. Our results suggest that the diffusion properties of ketamine have a significant effect on drug concentrations achieved within brain tissue during in vitro experiments. This information is vital to determine the ketamine concentration necessary for in vitro slice preparation to accurately reflect in vivo doses responsible for its antidepressant actions.